ANALISIS PENDAPATAN USAHA GULA AREN PADA MASYARAKAT YANG TINGGAL DI DALAM DAN DI SEKITAR HUTAN - Makkarennu Makkarennu; Muhammad Fikri Rum; Ridwan Ridwan (PERENNIAL, 2018)
Palm sugar as one of product of Non-Timber Forest Products (NTFPs) which contributes to communities living in and around forests. However, the use and processing of products is still tradistional managed so as to produce results that have not been maximized. This study aims to analyses the income of palm sugar product for farmer groups who living in and around forest. The location of the study was in forest farmer groups in Labuaja Village, Cenrana Sub-District, Maros Regency, South Sulawesi. Sampling was carried out on each farmer group consisting of 10 people in three farmer groups with the number of respondents as many as 30 people conducted by simple random sampling. Data analysis was carried out through qualitative descriptive analysis and quantitative analysis. The results showed that the income of each farmer palm sugar per year was Rp. 9,562,012.Key words: forest farmer group; fixed cost; income analysis; palm sugar; variabel cost